Estabilização de joelho de cães com fio de poliéster intra-articular, após desmotomia do ligamento cruzado cranial – avaliação ex vivo - Reinstein, Rainer da Silva (2022)
The incidence of the cranial cruciate ligament rupture (CCLR) in dogs is high, being considered the main arthropathy of the species. Once diagnosed, surgical stabilization is recommended and several authors indicate different treatments, being divided into intracapsular, extracapsular and osteotomies. There is still no consensus on the best form of stabilization and new studies are being developed seeking to create or improve existing techniques, making them more effective. The objective of this work is to present a technique for intra-articular stabilization of the knee, using a synthetic polyester implant. For this, thirty-two anatomical pieces from canine cadavers were separated into two groups, according to the animal's weight. We analyzed the drawer movement in three moments: intact cranial cruciate ligament (CCL), desmotomized ligament and post-surgical stabilization by the proposed technique. The results demonstrate a mean cranial displacement of the tibia in relation to the femur before desmotomy of 0.61±0.08 millimeters (mm), 2.61±0.08 mm after desmotomy and 0.68±0.08 mm after surgical stabilization (P<0.01). We conclude that the proposed technique is effective in stabilizing the joint in an ex vivo model of dogs after CCL desmotomy.